Literature Review: Potensi Pemanfaatan Minyak Alami Dalam Inovasi Formulasi Kosmetik - Arline Rahmadianti Kusumawardhani; Nur Komala Fitri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The utilization of natural oils as primary and additional raw materials has long been practiced in the cosmetics industry. Natural oils are known to be rich in nutrients and beneficial properties, making them suitable for the production of beauty and skincare products. The main objective of this literature review is to identify recent developments, identify and address issues that may arise in formulating products using natural oils, and explore opportunities in utilizing natural oils in cosmetic formulations. This literature review conducted by searching national and international journal articles from the period of 2012 to 2023, selecting those that were relevant to the topic and conducting a comprehensive analysis. Based on the literature review, it was found that natural oils have proven potential in innovating cosmetic formulations due to their natural and organic benefits, as well as being more environmentally friendly compared to chemical ingredients, although challenges that require solutions exist. Furthermore, through further research and innovation in the utilization of natural oils, superior and high-quality cosmetic formulations can be developed in the future.